2019
DOI: 10.11606/s1518-8787.2018052000646
|View full text |Cite
|
Sign up to set email alerts
|

Adequate control of hypertension among older adults

Abstract: OBJECTIVE To estimate the prevalence of adequate control of hypertension among older adults and to examine its association with predisposing and enabling factors and the need to use health services.METHODS The analysis was carried out with 4,148 participants (≥ 50 years) from the baseline of the Brazilian Longitudinal Study of Aging (ELSI-Brazil), who reported being hypertensive and using antihypertensive medication. Adequate control of hypertension was defined as systolic and diastolic blood pressure below 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
12
1
1
Order By: Relevance
“…It has been shown that health insurance users present higher rates of diagnosis and controlled hypertension [50, 51]. In Brazil, results from the ELSI study also showed a positive association between adequate BP control and the use of private healthcare [52]. As users of the public healthcare system in Brazil are mostly individuals with worse socioeconomic conditions, these results also suggest some influence of socioeconomic factors on the control of chronic diseases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown that health insurance users present higher rates of diagnosis and controlled hypertension [50, 51]. In Brazil, results from the ELSI study also showed a positive association between adequate BP control and the use of private healthcare [52]. As users of the public healthcare system in Brazil are mostly individuals with worse socioeconomic conditions, these results also suggest some influence of socioeconomic factors on the control of chronic diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Three studies with a population-based sample that evaluated only older people were found in the review, all in the southeast region, and the control ranged from 27% to 44.6% [53]. Recent data from the ELSI study, considering older people residing in 70 Brazilian cities, showed that only 51% had BP controlled [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, complementary actions are required to ensure adherence to the prescribed medication, the continuous care of the people treated, and the promotion of healthy habits [26]. In addition, improvements in population education and income may substantially contribute to SAH control [27].…”
Section: Discussionmentioning
confidence: 99%
“…The intervention group under pharmaceutical care demonstrated significant control of SBP and DBP, as well as glycemia, dyslipidemia, body mass index, and abdominal circumference [43]. In addition to pharmaceutical care, the Brazilian Longitudinal Study of Aging (ELSI-Brazil) showed that BP control is associated with education level, socio-economic status, a private health plan, and obesity [27]. Thus, pharmacist intervention is important to provide education of patient and to improve medication adherence of hypertensive and heart failure patients [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of social inequality are found in the majority of topics investigated, with the poorest or those with lower educational level affected most. Inequalities are observed in physical activity 7 , oral health status 8 , limitations to perform basic activities of daily living 9 , frailty 10 , adequate control of hypertension 11 , underutilization of medications due to financial reasons 12 , source of health care 13 , and capacity to work 14 . Social participation 15 and the fear of falling 16 are associated with the urban environment.…”
mentioning
confidence: 99%